Inhibition of Glyoxalase-I Leads to Reduced Proliferation, Migration and Colony Formation, and Enhanced Susceptibility to Sorafenib in Hepatocellular Carcinoma - Michel, Maurice; Hollenbach, Marcus; Pohl, Sabine; Ripoll, Cristina; Zipprich, Alexander (Frontiers in Oncology, 2019)
Background: Glyoxalase-I (Glo-I) is essential for detoxification of methylglyoxal (MGO), a byproduct of glycolysis. Overexpression of Glo-I has been linked to multi-drug resistance in cancer therapy. The aim of this study was to analyze Glo-I in hepatocellular carcinoma (HCC) and the effect of the multi-tyrosine kinase inhibitor sorafenib on Glo-I. Methods: Expression and specific activity of Glo-I was measured in human HCC samples, HCC-cell lines (HepG2, Huh7) and a hepatocyte cell line (AML 12). Cells were either treated with Glo-I inhibitors, ethyl pyruvate (EP, 1–20 mM) and BrBzGSHCp2 (1–10 μM), or sorafenib (2.5–10 μM) and protein expression (Western Blot), proliferation (WST-assay), migration (scratch assay), and colony formation (clonogenic assay) were assessed. Results: High expression of Glo-I was detected in human HCC tissue samples. Huh7 showed highest expression and activity of Glo-I and revealed highest proliferation compared to AML 12 and HepG2. Targeting Glo-I by EP or BrBzGSHCp2 led to significantly reduced proliferation (20 mM EP 24 h: 57 ± 12%), migration and colony formation. Glo-I inhibition by 20 mM EP resulted in reduced expression of PDGFR-β (18 ± 10%), VEGFR2 (46 ± 11%), VEGF (61 ± 10%), pERK/ERK (62 ± 6%), NF-κB (44 ± 12%) as well as stimulation of Nrf2 (243 ± 36%). Similar results were seen with BrBzGSHCp2. Sorafenib treatment revealed elevation of Glo-I (10 μM: 209 ± 25%) and MGO. Co-treatment of EP and sorafenib led to an additional reduction of proliferation compared to sorafenib alone. Conclusion: Glo-I is positively correlated with HCC proliferation. Inhibition of Glo-I reduced proliferation, migration, and colony formation. In turn, sorafenib increases Glo-I. Co-treatment using Glo-I inhibitors could enhance susceptibility of HCC to sorafenib.